Degrees of poverty: The relationship between family income background and the returns to education - Timothy J. Bartik; Brad J. Hershbein (W.E. Upjohn Institute for Employment Research, 2018)
Drawing on the Panel Study of Income Dynamics, we document a startling empirical pattern: the career earnings premium from a four-year college degree (relative to a high school diploma) for persons from low-income backgrounds is considerably less than it is for those from higher-income backgrounds. For individuals whose family income in high school was above 1.85 times the poverty level, we estimate that career earnings for bachelor's graduates are 136 percent higher than earnings for those whose education stopped at high school. However, for individuals whose family income during high school was below 1.85 times the poverty level, the career earnings of bachelor's graduates are only 71 percent higher than those of high school graduates. This lower premium amounts to 300,000 less in career earnings in present discounted value. We establish the prevalence and robustness of these differential returns to education across race and gender, finding that they are driven by whites and men and by differential access to the right tail of the earnings distribution.
Keywords: I24; I26; J24; J31; 330; inequality; return to education; career earnings profile; PSID; low-income